Calculus with analytic geometry - Zill, Dennis G. (Boston, Mass. : PWS Publishers, 1985)
This book is intended for a three-semester of four-quarter course in calculus for students of science, engineering, mathematics, and business.
1. Function -- 2. Limits of functions -- 3. The derivatives -- 4. Applications of the derivative -- 5. The integral -- 6. Application of the integral -- 7. Inverse trigonometric functions -- 8. Logarithmic and exponential functions -- 9. Techniques of integration.
Includes index.
Keywords: CALCULUS; GEOMETRY -- ANALYTIC